(untitled) (Revista Rupturas, 2016)
The current article analyses the representation of social protest; concerning the demands made by the educational sector in a sample of news reports that were broadcast on the Costa Rican newscast REPRETEL throughout May; 2014. This research is carried out using a methodological multimodal analysis standpoint and the main aim is to ascertain the different persuasive mechanisms used to portray protest in the education